TIC & TER. Stratégie numérique et qualité de service à la SNCF - Pierre-Henry Emangard (Netcom, 2015)
With ICTS, a new commercial strategy has been promoted by SNCF towards all its customers. Studying the Sud Loire Ocean sector, the paper shows that ICTS information services have been an alibi for lowering regional rail services quality and has lead to traffic decrease. This case shows that ICTS impacts are not these expected because they upgrade roughness and fuzzyness culture.